GE_GERICHTE A/3751/2007 vom 12. Oktober 2009 - GE Cour de justice (2009)
; IMMEUBLE(ART. 655 CC) ; VENTE ; DROITS DE MUTATION ; RÉDUCTION(EN GÉNÉRAL) ; CONTRAT D'ENTREPRISE ; CÉDULE HYPOTHÉCAIRE | LDE.8; LDE.8A; RDE.2.al2;